A case of lichen planus pemphigoides with autoantibodies to the NC16a and C‐terminal domains of BP180 and to desmoglein‐1. (6th October 2014) - Sekiya, A.; Kodera, M.; Yamaoka, T.; Iwata, Y.; Usuda, T.; Ohzono, A.; Yasukochi, A.; Koga, H.; Ishii, N.; Hashimoto, T.
Summary: Lichen planus pemphigoides (LPP) is a rare autoimmune blistering disease that occurs in association with lichen planus (LP). This report describes a 59‐year‐old Japanese female patient with LPP. The patient first showed LP lesions on her hands, and subsequently developed bullae on her extremities and erosions of the oral mucosa. The patient's serum was positive for IgG autoantibodies against the BP180 NC16a domain, the BP180 C‐terminal domain and desmoglein‐1. However, a serum sampled one and a half years before the diagnosis of LPP was negative for autoantibodies against BP180 NC16a and BP180 C‐terminal domains. These findings strongly suggest that the damage to the basal cells in the LP lesions exposed a sequestered antigen or formed neoantigens, leading to the production of pathogenic autoantibodies for LPP. Most of the previous cases of LPP have produced autoantibodies to the NC16a domain of BP180. This is the first case in which autoantibodies to the C‐terminal domain of BP180 were detected. The oral mucosal symptoms in this case may have been caused by autoantibodies to the BP180 C‐terminal domain. Abstract : What's already known about this topic? Damage to the basal cells in lichen planus may expose sequestered antigens or produce neoantigens, leading to autoantibody production. Autoantibodies to the NC16a domain of BP180 have been detected in most cases of lichen planus pemphigoides. What does this study add? This report demonstrates the presence of circulating autoantibodies to BP180 only after the appearance of bullae, suggesting the role of sequestered antigen exposure or neoantigens in the pathogenesis of the disease. The present case showed autoantibodies to the C‐terminal domain of BP180, which has never been reported, and showed that they may cause oral mucosal lesions.